KETIDAKAMANAN KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN DIMEDIASI KEPUASAN KERJA - Muhammad Ilham Syaputra; Praningrum, Praningrum (Jurnal Ilmiah Ekonomi Dan Bisnis, 2024)
Human resources are one of the most important elements in an organization. The more worried an employee is about job insecurity, the more it can reduce his performance. A good work environment can improve employee performance, and vice versa. The research was conducted to answer the gap in previous research that job insecurity and the work environment have nothing to do with employee performance. In this research model, the variable job satisfaction is added to be the most likely thing to use to find out and bridge the research gap. This research was conducted at Bengkulu City Printing. In the steps to analyze the incoming data, the researcher used Smart Pls 3.0 software, this was done because the number of respondents was 53 employees at Bengkulu City Printing.